Generasi Muda Membangun Desa Wisata (Studi: Desa Wisata Brayut, Sleman Yogyakarta) - Rizal, Derry Ahmad (Prodi Pengembangan Masyarakat Islam Fakultas Dakwah dan Ilmu Komunikasi UIN Mataram, 2017)
The village becomes a comfortable place to live, because it still looks beautiful and fresh air. The urban community who originally came from the village even flocked to leave their village to earn money. Long life in the city, it causes the boredom for the urban community and they miss the village that was ever occupied. Tourism village becomes one of the urban communities to release the longing for the village that once lived. Tourism village is intentionally designed, made a tourismplace with the concept of rural life in general. In the process of rural tourism development, it must all elements in the village to be built, including the young generation. Today, many young people do not care about their respective villages,whereas the young generation becomes the hope to be the next local wisdom. How is the role of the young generation in building a tourism village? The purposes are to find out how far the role of the young generation in building a tourism village, with various problems experienced by the young generation. This type of research used descriptive qualitative method, the approach that researcher used in this research was phenomenological approach. Researcher in this research tried to understand how the role of the young generation in developing tourism village and various problems faced by the young generation. How is the process towards becoming a tourism village?